Проблеми використання і найдійності вільного програмного забезпечення - Головань, С.М.; Нечипорук, В.В.; Щербак, Л.М. (Моделювання та інформаційні технології, 2010)
In work basic attention is spared free software and basic criteria are indicated on
the basis of which the author of free software passes to the programs the users. Basic
among these criteria is free distribution of source code, derivative product,
inviolability of author source code, absence of discrimination and purview license.
The questions of reliability of software are also considered at direction of exposure
and correction of errors of software.